(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article summarizes the results of research on the aesthetic assessment of water and recreational resources in the Aragatsotn Region of the Republic of Armenia with the aim of restoring the health and working capacity of the population, organizing tourist and recreational events․